2016
DOI: 10.17161/folklorica.v19i1.5721
|View full text |Cite
|
Sign up to set email alerts
|

The Crisis in Ukraine and the Split of Identity in the Russian-speaking World

Abstract: The events of 2014 in Ukraine triggered a wave of discussions and narratives rewriting history and reexamining allegiances and cultural affinities. Material for the study was drawn from Facebook, blogs and internet discussion forums, folk humor disseminated online, personal correspondence and participant observation. This essay discusses how opinions are formed in the diaspora and how they are affected by different sources of information. The attitude to events in Ukraine has turned into a litmus test in perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Ізраїльська фольклористка Л. Фіалкова у співпраці з М. Єленевською зафіксували російськомовний суспільний дискурс довкола реакції на вдягання ізраїльтянами родом з України футболок із зображенням С. Бандери [3]. Це дослідження підкреслює, який великий вплив на соціальні настрої може чинити трансляція патріотичних ідей через одягову культуру.…”
unclassified
“…Ізраїльська фольклористка Л. Фіалкова у співпраці з М. Єленевською зафіксували російськомовний суспільний дискурс довкола реакції на вдягання ізраїльтянами родом з України футболок із зображенням С. Бандери [3]. Це дослідження підкреслює, який великий вплив на соціальні настрої може чинити трансляція патріотичних ідей через одягову культуру.…”
unclassified
“…WhileBarrington et al (2002) have rejected the suggestion that ethnic Russians in the near abroad would support Russian political intervention in countries of their residence, in the current circumstances, it does not seem undeniable.In a modern global world, diaspora involvement in historical homeland conflicts has become a regular occurrence. Looking at the example of the Russian-speaking diaspora in Israel,Fialkova and Yelenevskaia (2015) have demonstrated that the Russia-Ukraine conflict has become widespread among Israeli Russophones and resulted in the split of their identity. Being based upon pro-Russian vs. pro-Ukrainian opposition, this split has incorporated vital aspects.…”
mentioning
confidence: 99%